Oncogenic HPV Types Infection in Adolescents and University Women from North Portugal: From Self-Sampling to Cancer Prevention. (28th November 2011) - Silva, Jani; Ribeiro, Joana; Sousa, Hugo; Cerqueira, Fátima; Teixeira, Ana Luisa; Baldaque, Ines; Osório, Teresa; Medeiros, Rui
Abstract : This study aimed to characterize the HPV infection status in adolescents and young university women in Portugal. The distribution of HPV genotypes was evaluated by PCR DNA genotyping after self-sampling collection from 435 women of exfoliated cervical cells using a commercial kit. We observed an overall frequency of HPV infection of 11.5%. Furthermore, HPV DNA prevalence was 16.6% in those young women that self-declared as sexually active. The more frequently detected HPV types were 31, 16, 53, and 61. Statistical analysis identified median age (OR = 3.56 ;P = 0.001 ), the number of lifetime sexual partners (OR = 4.50 ;P < 0.001 ), and years of sexual activity (OR = 2.36 ;P = 0.008 ) as risk factors for HPV acquisition. Hence, our study revealed that oncogenic HPV infection is common in young asymptomatic women Portuguese women, with a history of 2–5 sexual partners and over 2 year of sexual activity. Moreover, these results demonstrate that HPV detection performed in self-collected samples may be important to appraise better preventive strategies and to monitorize the influence of vaccination programmes within different populations.